Work organization and economic examination of breadwinning of rurality - Ferencz , Árpád; Kalmár, Rita (Applied Studies in Agribusiness and Commerce, 2009)
Agriculture has been and probably will be a significant branch in the south part of the Great Plain in the future as well. Besides the mass products and in many cases instead of them when forming the agricultural structure, this region has to pay more attention to the branches that were important in the past. Hungarian experts who are famous in foreign countries as well deal with these branches and they provide excellent products. The rules referring to these products are more liberal in the market places of the European Union and their development is not controlled by strict quota systems. In the south part of the Great Hungarian Plain a lot of unique products of excellent quality are produced. Here in this essay we would like to find the answer to the question how the two significant products of the southern part of the Great Hungarian Plain can provide the families with the income that they can live on.We aim at the economical examination of the cucumber grown in Méhkerék and asparagus of Homok. To do this we will apply the so called Standard Gross Margin. The agriculture of the states of the European Union is measured with the help of this method. It can also help us in the future to decide whether the different farms belonging to families are economically viable in Hungary.